Off-design performance modelling of a solar organic Rankine cycle integrated with pressurized hot water storage unit for community level application - Kutlu, Cagri; Li, Jing; Su, Yuehong; Pei, Gang; Riffat, Saffa (Elsevier, 2018)
Solar organic Rankine cycle (ORC) has advantages over common PV systems in view of the flexible operation even if solar radiation is unavailable. However, at present the dynamic performance of solar ORC with respect to the off-design behaviour of storage unit, expander, pump and heat exchanger is rarely reported. This paper investigates a medium-temperature solar ORC system characterized by evacuated flat-plate collectors and pressurised water storage unit. The main aim of the study is to investigate the performance of the system with consideration of transient behaviour of the thermal storage unit which results in off-design operation of other components. The other aim is adjusting the power output according to electricity demand throughout a day. The heat storage unit is analysed using one-dimensional temperature distribution model. A transient simulation model is developed including pump and expander models. To meet the electrical demands of different periods, the mass flow rate of heat source is adjusted for controlling the evaporation temperature. Moreover, sliding pressure operation control strategy of the ORC is implemented to meet variable heat source temperature. A 550 m2 solar collector area and a 4 m diameter and 7 m height pressurized water cylinder are used in simulation. Produced work is controlled and the results are matched with the demands. Produced work from the expander under the given conditions are 47.11 kWh in day time, 70.97 kWh in peak period and 31.59 kWh after midnight.